Abortion in modern health care: Considering the issues for health‐care professionals. Issue 2 (28th January 2016) - Smyth, Dawn; Lane, Paula
Abstract: This paper explores the challenging and contentious issue of abortion and its ethical, legal and political significance regarding public health. It is intended as an educational guide for health‐care professionals. A comprehensive search strategy of international health, law and political source materials was undertaken in order to benchmark from international approaches to abortion. Test cases illustrate the application of legislation, ethical, political and cultural issues surrounding abortion. Abortion is a complex contemporary issue where balancing the well‐being of both the mother and the unborn has prompted considerable international discourse. The right to life of the woman and the unborn continues to lie in tension. Ambiguity surrounds the concept of personhood, and the inception of human life prevails across many International jurisdictions. Health‐care professionals must be well informed in order to respond safely and appropriately to a diverse range of clinical scenarios in which decisions regarding abortion are required. Research and evidence of test cases will better inform how abortion issues evolve and are managed. Ultimately, the abortion debate requires a balance between legislation and clinical governance.